DNA Binding Activity of the Herpes Simplex Virus Type 1 Origin Binding Protein, UL9, Can Be Modulated by Sequences in the N Terminus: Correlation between Transdominance and DNA Binding - Chattopadhyay, Soma (American Society for Microbiology, 2006)
UL9, the origin binding protein of herpes simplex virus type 1, is a member of the SF2 family of helicases. Cotransfection of cells with infectious viral DNA and plasmids expressing either full-length UL9 or the C-terminal DNA binding domain alone results in the drastic inhibition of plaque formation which can be partially relieved by an insertion mutant lacking DNA binding activity. In this work, C-terminally truncated mutants which terminate at or near residue 359 were shown to potentiate plaque formation, while other C-terminal truncations were inhibitory. Thus, residues in the N-terminal region appear to regulate the inhibitory properties of UL9. To identify which residues were involved in this regulation, a series of N-terminally truncated mutants were constructed which contain the DNA binding domain and various N-terminal extensions. Mutants whose N terminus is either at residue 494 or 535 were able to bind the origin efficiently and were inhibitory to plaque formation, whereas constructs whose N terminus is at residue 304 or 394 were defective in origin binding activity and were able to relieve inhibition. Since UL9 is required for viral infection at early but not late times and is inhibitory to infection when overexpressed, we propose that the DNA binding activities of UL9 are regulated during infection. For infection to proceed, UL9 may need to switch from a DNA binding to a non-DNA binding mode, and we suggest that sequences residing in the N terminus play a role in this switch.